2006
DOI: 10.1149/1.2257872
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Structural and Electrical Properties of a-SiCO:H as a Diffusion Barrier to Copper

Abstract: In this study, we attempted to deposit low dielectric constant a-SiCO:H as a copper diffusion barrier by the plasma-enhanced chemical vapor deposition method using an organosilicon precursor, bis͑trimethylsilylmethane͒ ͑BTMSM, C 7 H 20 Si 2 ͒. The dielectric constant of the a-SiCO:H films increased from 2.54 to 3.25 as the deposition temperature was increased from room temperature to 280°C. The refractive index increased gradually with increasing deposition temperature, indicating that the film has a denser st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…5 Silicon oxycarbide ͑SiC x O y ͒ is also the focus of extensive study due to applicability in Si chips, such as low-k dielectric, etch-stop and passivation layers. 6 The present investigators have recently demonstrated strong luminescence around 1540 nm, Er-doped a-SiC x O y thin films. 7 In light of the challenges in development of Si white light emitters, particularly in achieving thermally stable emission with desired chromaticity, the current investigators are exploring amorphous a-SiC x O y as active medium for white light emission.…”
mentioning
confidence: 59%
“…5 Silicon oxycarbide ͑SiC x O y ͒ is also the focus of extensive study due to applicability in Si chips, such as low-k dielectric, etch-stop and passivation layers. 6 The present investigators have recently demonstrated strong luminescence around 1540 nm, Er-doped a-SiC x O y thin films. 7 In light of the challenges in development of Si white light emitters, particularly in achieving thermally stable emission with desired chromaticity, the current investigators are exploring amorphous a-SiC x O y as active medium for white light emission.…”
mentioning
confidence: 59%
“…The annealed sample exhibits three subpeaks at 97.7, 102.00, and 104.26 eV, which are assigned to SiC, C-Si-O, and Si-O x bonds, respectively, obtained from Fig. 16,26,27,30 On the other hand, in the case of the C 1s annealed ͑600°C͒ film, a new phase appeared at 287.45 eV, which is attributed to C-H/C-O-H bonding. 16,17 Due to annealing at 600°C, the chemical properties of the film surface change, which could enhance the chemical shift ͑corresponding to the Si 2p BE͒.…”
Section: B X-ray Photoelectron Spectroscopymentioning
confidence: 93%
“…16,17,[26][27][28] In order to minimize the interference between the peaks during deconvolution, all spectra have been fitted with equal line widths ͑full width at half maximum, FWHM͒ of the concerned individual peak, thereby reducing the number of free parameters and yielding a more stable result. 16,17,[26][27][28] In order to minimize the interference between the peaks during deconvolution, all spectra have been fitted with equal line widths ͑full width at half maximum, FWHM͒ of the concerned individual peak, thereby reducing the number of free parameters and yielding a more stable result.…”
Section: B X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…The ratio of the suboxide bonds can indicate the changes of k value. 44,45 The sub-oxide bonds has less angle (<144 o ), and it occupy the small volume, so it lead to the reducing of air aperture in the firm and increase the k value. In the FIB assisted chemical planar de-layered samples, there is much sub-oxide bonds with angle (<144 o ), and the k may be higher than polisher samples.…”
Section: Methods 1: Chemical Etchingmentioning
confidence: 99%